Development of a Web-Based First-Person Game of the Legend of Toar and Lumimuut Using Three.js - Delon Daniel Wolayan; Benny Pinontoan; Edwin Tenda; Stephano Caesar Wenston Ngangi; Mahardika Inra Takaendengan; Dodisutarma Lapihu (PT. Tech Cart Press, 2026)
The legend of Toar and Lumimuut is a foundational Minahasan narrative that is increasingly unfamiliar to younger digital audiences. This research develops Toar & Lumimuut: Legend of Minahasa, a browser-based first-person puzzle adventure game that adapts the legend into an interactive 3D experience using Three.js. The study applied an iterative Game Development Life Cycle consisting of initialization, pre-production, production, alpha testing, beta testing, and release. The game contains two narrative levels: the Coast of Mount Wulur Mahatus and Mount Lolombulan. Each level integrates puzzle mechanics with story progression, including sacred torch activation, stone pillar sequencing, prophecy fragment ordering, sacred seed planting, and eternal flame activation. Technical implementation includes procedural terrain generated with Perlin noise, animated GLB characters and props, an NPC dialogue and quest system, inventory management, bilingual English-Indonesian text support, and browser-based deployment without installation. Functional validation used black box testing with 68 test cases covering movement, interface controls, dialogue, puzzles, timers, game-over states, and level transitions. All test cases passed, producing a 100% functional success rate. User acceptance testing with 15 respondents aged 19 to 21 produced an overall score of 84.44%, categorized as very good. Compatibility testing on Google Chrome, Mozilla Firefox, and Microsoft Edge showed that the game remained playable across three laptops without dedicated GPUs. The results indicate that Three.js can support accessible cultural game development while preserving local folklore through meaningful interactive gameplay.